Feasibility of Aspects of Content, Language and Usefulness in the Development of Partnership Model-Based Student Learning Activity Instruments in Elementary Schools - Arif Widodo; Prayogi Dwina Angga; Muhamad Syazali; Umar Umar (Peneliti.net, 2022)
The existence of instruments in measuring student learning activities plays a very important role. This study aims to determine the feasibility of aspects of content, language and usefulness in developing student learning activity instruments based on the partnership model in elementary schools. The type of research used is development research. The development model used is the 4D model with define, design, develop and disseminate stages. The instruments used in data collection included: needs analysis questionnaires, instrument validation sheets by evaluation experts, instrument validation sheets by linguists and instrument validation sheets by users. The results showed that the feasibility of student activity sheet instruments from the content aspect got a score of 86, the language aspect got a score of 82, and the usability aspect got a score of 88. The validation results on the partnership model based learning activity sheet instrument show that from the aspect of content and usefulness the instrument is categorized very feasible, while from the aspect of language it is included in the feasible category. Based on the results of the validation test, it can be concluded that the partnership model-based instrument is feasible to use to measure student learning activities in elementary schools